Особливості анатомічної будови листової пластинки Laelia sincorana Schltr. та Laelia purpurata Lindl. у зв’язку з еколого-кліматичними умовами виростання - Yaroslavskaya, J.M.; Ivannikov, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
Anatomical structure of leaf plate of two species of Laelia Lindl. – L. sincorana Schltr. and L. purpurata Lindl. has been analyzed. Particular attention is given to the genus understanding of relations between epidermic leaf layer structure and environmental-climatic conditions of native habitats.